Muhammad Basiuni Imran: Tokoh Legendaris Islam, Sambas, Kalimantan Barat Abad 20 M - Wendi Parwanto (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2023)
Research on ulama in West Borneo is important because it hasn’t been widely studied by researchers. Based on these reasons, the researcher is interested in studying this theme further. ‎This study uses the genealogy of knowledge theory and with a historical approach. The ‎conclusion of this article is a‎ Muhammad Basiuni Imran's thoughts were much influenced by Muhammad Rasyid Ridha in particular the idea of ​​Islamic reform, and these ideas were accentuated in the Sambas region, especially in reforming education.